Improving the reliability of cardiological diagnostics of arrhythmias using stochastic parameters of spectral dynamics of rhythmograms - Sokol, Yevgen I.; Shapov, Pavel; Kulichenko, Viacheslav; Tomashevskyi, Roman; Gorbulitch, Alexandr; Muzhychuk, Oleksii (Національний аерокосмічний університет ім. М. Є. Жуковського "Харківський авіаційний інститут", 2020)
The article presents the results of a theoretical analysis of the parameters of a two-dimensional autocorrelation function and it`s filtering in time, the results of dynamic modeling of arrhythmia identification procedures using training rhythmograms. The possibility of intellectualization of identification procedures using the statistical procedure of Wald's sequential analysis has been proved. Results of parametric identification of cardiac conditions by changes in the characteristics of correlation-spectral non-stationarity of rhythmograms in a sliding observation window
Keywords: rhythmogram; atrial fibrillation; stochastic parameters; autocoherence model; non-stationarity; ритмограма; фібриляція передсердь; стохастичні параметри; модель автокогерентності; нестаціонарність